Relationship of Work Environment and Employee Performance: Study at PT. Energia Transmedia - Rini Ardista; Netti Natarida Marpaung (International Journal of Education, Information Technology, and Others, 2022)
This study aims to determine and analyze the effect of the work environment and employee performance at PT. Energia Transmedia. This study uses a quantitative method with a descriptive approach. The variables used in this study are the Work Environment variable (X), and the Employee Performance variable (Y). The data sources used consisted of primary data, namely data obtained directly from research respondents through questionnaires, interviews, and observations. The population and sample in this study were employees of PT. Energia Transmedia. The test was conducted using SPSS 25. Based on the results of the partial test (t test) it can be concluded that the work environment variable has a significant influence on employee performance because the t-count (5.256) > t-table 277 with a significance of 0.000 <0.05. The adjusted R square value obtained is 0.479, indicating that around 47.9% of the employee performance variable (Y) can be explained by the work environment variable (X). Or practically it can be said that the contribution of the work environment to the employee performance variable is 47.9%.